Development of EEG signal processing algorithms and control mechanism for brain-computer interface game - Lin, Jiangnan (2014)
The target of our project is to develop a game controlled by attention based brain wave signals. My individual project developed a C# program to gather the user’s brain wave signal through the commercial electroencephalography (EEG) device – Emotiv Epoc Headset and process the data by the DSP function to generate an 3-level attention indication value. Game player can use the attention level indication value to control the game play. The DSP function apply the Fast Fourier Transform (FFT) and signal conjugation to convert the time domain EEG input signal into frequency domain data. Based on the calculated frequency spectrum, program generates the attention level indication value and passes the value to the game control block. The EEG game can be controlled with the attention level measured from this program.